Onward Migration Aspirations and Transnational Practices of Migrant Construction Workers Amidst Economic Crisis: Exploring New Opportunities and Facing Barriers. (25th December 2020) - Dimitriadis, Iraklis
Abstract: Considering onward migration aspirations of Albanian migrants in Italy and Greece, this article investigates the reproduction of transnational practices in relation to preferred destinations before new settlements take place. Drawing on qualitative data, it introduces the concept of explorative transnational practices and sheds light on the interplay between aspirations and transnationalism, showing how the desire to leave the first country may be shaped by transnational ties, and how this may trigger occasional transnational physical activity to explore new destinations. On one hand, this version of transnational mobility may engender remigration, but, on the other, this may be transformed into income‐oriented work trips due to structural constraints (legal status, immigrant networks) and a lack of linguistic and economic capital, as well as other factors such as integration processes, intergenerational relationships and experiences in new destinations. This questions the very presumptions of the transnationalist approach that underscore agentic dimensions of transnational migrants.